Oral Conditions as Risk Factors for Low Oral Health-Related Quality of Life Among the Elderly Population in Yogyakarta, Indonesia - Agustina, Dewi; Hanindriyo, Lisdrianto; Chrismawaty, Bernadetta Esti; Naritasari, Fimma (European Journal of Dentistry, 2022)
Objective Approximately 70% of the elderly population living in Yogyakarta, Indonesia, has a low oral health-related quality of life (OHRQoL). This study aimed to identify the risk factors for low OHRQoL in the elderly population of Yogyakarta.Materials and Methods Oral Hygiene Index Simplified (OHI-S), Community Periodontal Index, Decayed, Missing, and Filled Teeth (DMFT) Index, and the number of natural occluding pairs (NOP) were assessed for 153 participants aged ≥ 60 years. Xerostomia, hyposalivation, and OHRQoL were also examined using Xerostomia Inventory (XI), unstimulated spitting whole saliva collecting method, and Geriatric Oral Health Assessment Index (GOHAI) questionnaire, respectively. OHRQoL was categorized as low, moderate, and high.Statistical Analysis Bivariate and multivariate tests were conducted to identify the risk factors for low OHRQoL.Results Initial analysis of characteristics of participants revealed that hyposalivation, xerostomia, periodontal pocket, high DMFT, NOP ≤ 5, poor OHI-S, and low OHRQoL were experienced by 40 (26.1%), 92 (60.1%), 39 (25.5%), 110 (71.9%), 112 (73.2%), 44 (28.8%), and 108 (70.6%) participants, respectively. Relative risk (RR) and p values for hyposalivation, xerostomia, periodontal pocket, high DMFT, NOP ≤5, and poor OHI-S were found to be at 1.573 (CI 0.681–3.637) and 0.225; 2.532 (CI 1.255–5.108) and 0.006; 0.846 (CI 0.391–1.830) and 0.606; 1.759 (CI 0.843–3.670) and 0.110; 1.133 (CI 0.522–2.461) and 0.008; and 2.723 (CI 1.293–5.734) and 0.632, respectively. Multivariate tests showed that xerostomia and NOP ≤5 had RR of 2.519 (CI 1.221–5.195) and 2.536 (CI 1.175–5.477), respectively.Conclusions Overall, elders with xerostomia or NOP ≤ 5 had 2.5 times higher risk of having a low OHRQoL.
Keywords: dental occlusion; quality of life; xerostomia